The dividing wall: Ephesians and the integrity of the Corpus Paulinum - Wright, Martin (Library of New Testament studies, 2021)
Cover -- Series -- Title -- Copyright -- Contents -- Tables -- Acknowledgements -- Abbreviations -- Introduction: The dividing wall -- Part One Canon and countercanon -- 1 The formation of the Corpus Paulinum -- 2 The dissolution of the Corpus Paulinum -- Part Two Reading Paul in Ephesians -- 3 From estrangement to reconciliation -- 4 The body and the Corpus -- Conclusion: Corpus conpactum et conexum -- Bibliography -- Index of Authors -- Index of Biblical References -- Index of Subjects.